Aquatic ecosystems as a final receptor of atmospheric organic particulate-bound pollutants: a plea for the integration of aquatic ecotoxicology into the risk assessment of air pollution - Marc Wollenweber; Markus Schmitz; Saeed S. Albaseer; Sabrina Schiwy; Natalie Reininger; Werner Brack; Jörg Oehlmann; Joachim Curtius; Alexander L. Vogel; Henner Hollert (Environmental Sciences Europe, 2025)
Abstract Background Air pollution has detrimental effects on human health and is estimated to cause millions of premature deaths worldwide each year. The effects of polluted air on human health, ranging from respiratory and cardiovascular disorders to cognitive impairment, have been discussed extensively. Air pollution also adversely affects terrestrial and aquatic ecosystems through the deposition of harmful chemicals on land and water bodies. This holds especially true for aquatic ecosystems, in particular surface water habitats, which serve as a final receptor of organic pollutants. Main body Over the past decades, a large knowledge base has been built up on the atmospheric transport and transformation of airborne pollutants. Several atmospheric deposition pathways have been identified by which airborne pollutants enter aquatic ecosystems, where they disperse and expose aquatic organisms. While past and current risk assessment has established sound strategies to reduce local and global air pollution, there are still several blind spots with respect to ecological health. This leads to an information gap regarding the mechanistic understanding of how airborne pollutants impact ecosystems, their biota, and the role of atmospheric deposition on this process. However, ecotoxicological considerations are important because air pollution contains a large number of organic pollutants, which pose a threat to aquatic biota. Therefore, we believe that current state of air pollution risk assessment would greatly benefit from the interdisciplinary approach of combining atmospheric research and ecotoxicological testing strategies. The use of effect-based methods from aquatic risk assessment can leverage our knowledge of the effects of air pollution on aquatic ecosystems and assist to decide on meaningful risk strategies. Conclusion In this opinion paper, we critically review the current knowledge on aquatic ecosystems as a final receptor of atmospheric pollutants and present an approach on how to advance the integration of aquatic ecotoxicology into risk assessment of air pollution in the future.